2019
DOI: 10.1152/jn.00170.2019
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor subunit α7-knockout mice exhibit degraded auditory temporal processing

Abstract: The CHRNA7 gene that encodes the α7-subunit of the nicotinic acetylcholine receptor (α7-nAChR) has been associated with some autism spectrum disorders and other neurodevelopmental conditions characterized, in part, by auditory and language impairment. These conditions may include auditory processing disorders that represent impaired timing of neural activity, often accompanied by problems understanding speech. Here, we measure timing properties of sound-evoked activity via the auditory brainstem response (ABR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 78 publications
1
45
0
Order By: Relevance
“…Application of ACh to the IC affects the responses to auditory stimuli of a majority of IC neurons (Watanabe and Simada, 1973 ; Farley et al, 1983 ; Habbicht and Vater, 1996 ). Such effects can modify temporal processing and forward masking (Felix et al, 2019 ). Supporting the idea of widespread effects of ACh in the IC, both nicotinic and muscarinic ACh receptors are present throughout the IC, as is acetylcholinesterase, the enzyme that degrades ACh (Shute and Lewis, 1967 ; Cortes et al, 1984 ; Glendenning and Baker, 1988 ; Henderson and Sherriff, 1991 ; Happe and Morley, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of ACh to the IC affects the responses to auditory stimuli of a majority of IC neurons (Watanabe and Simada, 1973 ; Farley et al, 1983 ; Habbicht and Vater, 1996 ). Such effects can modify temporal processing and forward masking (Felix et al, 2019 ). Supporting the idea of widespread effects of ACh in the IC, both nicotinic and muscarinic ACh receptors are present throughout the IC, as is acetylcholinesterase, the enzyme that degrades ACh (Shute and Lewis, 1967 ; Cortes et al, 1984 ; Glendenning and Baker, 1988 ; Henderson and Sherriff, 1991 ; Happe and Morley, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Staining for β4 nicotinic cholinergic receptor subunits is heaviest in layer 2 of the IClc, with moderate expression in the ICc and less in the ICd (Gahring et al, 2004 ). These receptors have recently been reported to aid in the modulation of spike timing and forward masking in the IC (Felix et al, 2019 ). The IClc has also been noted for its comparatively high levels of the α7 nicotinic receptor subunit and high levels of acetylcholinesterase (Happe and Morley, 2004 ; Dillingham et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, in vivo studies have shown that nicotinic drugs alter the gain of input-output functions in IC neurons (Farley et al, 1983;Habbicht & Vater, 1996), and human psychophysics studies indicate that nicotine improves performance in auditory attention and discrimination tasks (Knott et al, 2012;Smucny et al, 2016;Pham et al, 2020), an effect partly attributable to alterations in the IC (Askew et al, 2017). In addition, temporal coding of auditory stimuli is degraded in the IC of α7 knockout mice (Felix et al, 2019). However, despite the importance of nAChRs to auditory processing, the cellular mechanisms by which nAChRs influence the excitability IC neurons remain largely unknown.…”
Section: Introductionmentioning
confidence: 65%
“…Growing evidence indicates that cholinergic signaling through nicotinic acetylcholine receptors (nAChRs) critically shapes sound processing in the central auditory system (Goyer et al, 2016;Askew et al, 2017;Felix et al, 2019;Zhang et al, 2021). The inferior colliculus (IC), the midbrain hub of the central auditory system, receives extensive input from cholinergic neurons in the pontomesencephalic tegmentum (PMT; , and expresses several nAChR subunits, including α3, α4, α7, β2, β3, and β4 (Clarke et al, 1985;Wada et al, 1989;Morley & Happe, 2000;Whiteaker et al, 2002;Salas et al, 2003;Gahring et al, 2004;Happe & Morley, 2004;Bieszczad et al, 2012;Sottile et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Receptor binding indicates that SOC nuclei have high levels of cholinergic receptors (Morley and Happe, 2000;Gahring et al, 2004;Happe and Morley, 2004). Developmental knock-out of alpha-7 nicotinic receptors suggests that ACh may contribute to temporal processing in the superior paraolivary nucleus (Felix et al, 2019). We have shown previously that, in the MNTB, ACh affects suprathreshold response magnitude, enhances near-threshold level discrimination, and enhances coding for signal in noise (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%